MORPHOGENESIS AND ECOGENESIS OF BIVALVES IN THE PHANEROZOIC - Nevesskaja L.A. (My University, 2003)
The morphology, systematics, and ecology of bivalves are discussed. Changes in the taxonomic composition and morphogenesis of this group in the Phanerozoic are traced. Several ethological-trophic groups are characterized, and changes in their taxonomic composition over time are revealed. Bivalve communities dominating different geological periods are characterized. In the Phanerozoic, the taxonomic diversity of bivalves gradually increased. This increase was interrupted by a drop in taxonomic diversity in the Early Triassic. The majority of ethological-trophic groups are known to have appeared in the Early Paleozoic, but it is only from the Late Paleozoic onwards that bivalves became dominant or common organisms in all zones of the continental shelf.